Cytotoxic Effect of Trypanosoma cruzi Calcineurin B Against Melanoma and Adenocarcinoma Cells In Vitro - Mayela Serrano-Rodríguez; Jorge E. Araya; Mauro Cortez; Patricio R. Orrego (Advances in Pharmacological and Pharmaceutical Sciences)
Chagas disease caused by the obligate intracellular flagellate protozoan Trypanozoma cruzi infects about 6 million people. From the 1930s to the present, the antitumor capacity of T. cruzi has been studied; however, the identification of the responsible molecules for this effect remains undiscovered. Calcineurin, a calcium/calmodulin-dependent serine/threonine phosphatase, is a heterodimer consisting of a catalytic subunit (CaNA) and a regulatory subunit (CaNB). It has been described that T. cruzi CaN is involved in the cell invasion and proliferation of the parasite. Recently, extracellular human CaNB has been demonstrated to be capable of inhibiting tumor growth cells, conferring an antitumor effect; however, the extracellular role of T. cruzi CaNB (TcCaNB) is still unknown. The objective of this work was to investigate the antitumor potential of TcCaNB by interacting with membrane proteins and evaluating its effects on the viability, proliferation, and morphology of tumor cells in vitro. Additionally, the possible mechanism of action of TcCaNB was explored. Murine melanoma (B16-F10), human cervical adenocarcinoma (HeLa), and African green monkey kidney epithelial (Vero) cell lines were employed for in vitro assays. Far Western blot and immunofluorescence were performed to assess the interaction of TcCaNB with membrane proteins, and the effect of TcCaNB on cell viability and proliferation was evaluated using the MTS assay and the CyQUANT NF assay, respectively. The effect of the caspase inhibitor Z-VAD-FMK on TcCaNB-stimulated tumor cells was investigated to determine if TcCaNB-induced cell death was associated with apoptosis. To assess cell cycle progression, TcCaNB-treated cells were analyzed by flow cytometry. In this study, the results showed an interaction of TcCaNB with cell membrane proteins in B16-F10 and HeLa tumor lines, indicating that TcCaNB is capable of decreasing viability and proliferation of B16-F10 and HeLa cells, with no significant effect observed in Vero cells. Furthermore, morphological changes were observed in tumor cells treated with TcCaNB. DNA fragmentations and inhibition of caspases with Z-VAD-FMK partially counteracted the cytotoxic effects of TcCaNB on tumor cells, suggesting that TcCaNB-induced cell death might be associated with apoptosis. Additionally, TcCaNB caused S phase cell cycle arrest in HeLa cells, with an increase in the sub-G1 population indicative of apoptosis, while no significant effects were observed in Vero cells.